Behaviour of CFST column to H-section beam connections with T-shaped vertical anchorage. Issue 2 (1st February 2020) - Liu, Jiepeng; Li, Binyang; Zhou, Xiang; Yang, Yuanlong; Cheng, Wei; Chen, Y. Frank
Abstract: Three large-scale connections between square concrete-filled steel tubular (CFST) columns and H-section steel beams were tested. T-shaped vertical anchorage was used as the embedded elements and both static and seismic behaviours of the connections were tested in this study. The experimental parameters include length and location of T-shaped vertical anchorage. Based on the experimental data, the strength, ductility, stiffness degradation, and energy dissipation of the connections were calculated. The test results show that the connections exhibit good static and seismic behaviours. Furthermore, a parametric study was conducted using the finite element method where the considered parameters include the height and depth of end anchorage, and the thickness of vertical plate. Based on the study results, a preliminary design method is proposed, which includes the design formulae for calculating the thickness of vertical plate, the thickness of end anchorage, and the punching shear capacity of concrete. In conclusion, with a proper design, the connections with T-shaped vertical anchorage can be reliably used in practical applications.